การพัฒนานวัตกรรมการเรียนรู้เพื่อส่งเสริม สมรรถนะการวิจัยสำหรับนักศึกษาสาขาการศึกษา มหาวิทยาลัยราชภัฏ - นวกิจไพฑูรย์, นิลรัตน์; เลิศไกร, รศ.ดร.ปัญญา; เอียบสกุล, ดร.จริยา (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
Abstract The objective of this research was to develop innovation learning model to promote research competency of students from faculty of education at Rajabhat University. Research and development processes are divided into 3 steps. First, to study the fundamental and other relevant informations. Second, to design and develop a learning model. Third, to evaluate the model. The research sample were 30 students from faculty of education at Nakhon Si Thammarat Rajabhat University selected by simple random sampling. The instruments were 1) The 60 –Item test to measure the research knowledge, reliability of test KR-20 was .87. 2) Attitude questionnaire, and characteristics of research , reliability of test α was .85. 3) The satisfaction questionnaire on the learning model , reliability of test α was .92 . 4) The scoring rubric to assess research competency skills and 5) The research competency according to Thailand's teacher interview. The research results are as followed: 1. The developed innovation learning model to promote research competency is called "Ruk Rien Pien Rhu" or "Love what you learn and reflect on what you do." Learning activities included 4 steps : 1) Love 2) Learning 3)Doing: which are the steps that could be applied into 2 small steps which are practical application, and evaluation and improvement process. Lastly, step 4 is Reflection. The quality of learning management model score was in the range of 83.12 / 82.48. 2. The results of the evaluation of the learning model for promotion of research competency found that the scores in research competency skills of the students were higer that a set criteria. The evaluation of research competency according to Thailand's teacher council standards revealed that the students were able to deliver research results and modified into teaching methods. In addition, they were able to conduct researches in order to further develop learning systems for teachers and students. The scores demonstrated that the students were satisfied with the learning model at a very satisfactory range.